Emancipatory Discourse in the Literary and Critical Works by Eliza Orzeszkowa and Nataliia Kobrynska - Spatar, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Aim. The article is devoted to the study of world-view and axiological vectors in the emancipatory discourse of E. Ozheshko and N. Kobrynska. The article deals with the analysis of common approaches to the presentation of emancipatory ideas in the literary and critical works by E. Orzeszkowa and N. Kobrynska, in particular, with the comprehension of the women’s role in the family and society, their opportunities to study and work on a parity basis with men. Both writers called for the formation of a new social consciousness in order to overcome established patriarchal norms and customary stereotypes through education and enlightenment. The similarity of world-view and aesthetic views, artistic and semantic parallels in the authors’ works is due to the consonant life axiology and the declaration of sometimes too radical views. Methods. For the comparative analysis, a number of basic scientific methods were used, including historical and literary, typological and biographical approaches. Results. Through the comparative analysis, the following main issues through which the writers declared world-view, spiritual and moral changes were identified: the need for a thorough education, the education of erudite female intellectuals, the social and professional integration of women as active participants and reformers, rather than passive observers, the formation of a new social consciousness. Scientific novelty. An attempt is made to make a comparative analysis of the emancipatory discourse in the literary and critical works of women writers. The author’s vision of the special function of women in social, spiritual and intellectual contexts is outlined.